FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, LOCUS OF CONTROL PADA FINANCIAL BEHAVIOUR GENERASI Z (Mahasiswa Jurusan Manajemen FEB UPN Veteran Jakarta) - Sausan Annisa Fathya (2022)
The research used a quantitative study to examine the influence of financial knowledge, financial attitude, locus of control on the financial behaviour of generation Z. The students majoring in Management FEB UPN Veterans Jakarta in the study as samples. Sample selection using the Slovin formula with a simple random sampling method obtained a total sample of 240. Hypothesis testing in research conducted with Multiple Regression Analysis assisted by SmartPLS 3.0 program. The result is that there is a positive influence on financial knowledge on financial behaviour, there is a positive influence on financial attitude towards financial behaviour, but there is no positive influence on locus of control on financial behaviour.